Artificial cognition systems - Loula, Angelo 1977-; Gudwin, Ricardo 1967-; Queiroz, Joao 1963- (Gale virtual reference library, 2007)
"This book presents recent research efforts in Artificial Intelligence about building artificial systems capable of performing cognitive tasks. A fundamental issue addressed in this book is if these cognitive processes can have any meaningfulness to the artificial system being built"--Provided by publisher.